Optimizing the Supercritical Carbon Dioxide Extraction of Hibiscus Flower Essential Oil using Response Surface Analysis - Alanazi, Tahani Y. A. (Engineering, Technology & Applied Science Research, 2024)
The development of Supercritical Fluid Extraction (SFE) has opened the door to the harvesting of plants for a wide range of chemical compounds. This study distilled essential oil from hibiscus flowers utilizing the supercritical CO2 method. Different extraction parameters, including pressure (100-300 bar) and temperature (300-350 K), were studied to visualize how they affected oil recovery. Response surface analysis was used to fine-tune the extraction process. The chemical composition of the recovered oil was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). According to the findings, 13.11% per 80 g of dry flowers is the ideal oil extracted from Hibiscus flowers, using SFE at 200 bar pressure and 325 K extraction temperature. Six compounds were provisionally identified in the extracted oil from hibiscus flowers under optimum SFE conditions.